Clinical, biomechanical and histological study on oophorectomy induced menopause - Bordinhon, Maristela; Müller, Sérgio Swain; Silva, Maeli Dal Pai (Sociedade Brasileira de Ortopedia e Traumatologia, 2014)
Objective:To investigate the clinical implications as well as biomechanical and histological changes and in bone tissue induced by ovariectomy in 64 rats.Methods:The rats were divided into two groups: bilateral oophorectomy or placebo, and subdivided into four subgroups, according to time postoperatively: three, six, nine and 12 months. The weight of the animals at the time of sacrifice was taken into consideration. The biomechanical study was performed on the right tibia, to the maximum load and stiffness coefficient. For the histological study we calculated the trabecular bone of the left tibia. Statistical analysis of body weight and mechanical properties was performed by variance analysis, complemented with Tukey's multiple comparison tests; and trabecular area, the non-parametric variance analysis.Results:Ovariectomy-induced menopause caused an increase in body weight, reduction of diaphyseal bone resistance at six months of hormone deprivation, but this effect is equalized over time by aging; bone stiffness was smaller in the ovariectomized group and reduction of bone mass occurred.Conclusion:The removal of the ovaries produced systemic alterations, characterized by metabolic changes that caused weight gain and changes in bone tissue, associated with alteration of the mechanical profile and reduced bone mass. Level of Evidence I, Clinical Study.
Keywords: Ovariectomy; Rats; Female; Biomechanics; Histology; Osteoporosis, postmenopausal